Network meta-analysis on efficacy and safety of different anti-CGRP monoclonal antibody regimens for prophylaxis and treatment of episodic migraine. (2nd November 2021) - Shi, Min; Guo, Jun; Li, Zhaoying; Sun, Honghui; Yang, Xuhong; Yang, Dongdong; Zhao, Huan
ABSTRACT: Background: Currently, studies have shown that anti-CGRP monoclonal antibodies are effective drugs for the prophylaxis and treatment of episodic migraine. Therefore, for the first time, we classified and concluded 10 treatment regimens according to the different doses, drugs, routes of administration, and courses of treatment, so as to provide a reference for further clinical studies. Methods: We studied relevant randomized controlled trials (RCTs) published before August 2020 on PubMed, Embase, Ovid MEDLINE, Web of Science, and the Cochrane Central Register of Controlled Trials. Results: Eleven RCTs involving 6397 patients were included in our analysis. Network meta-analysis results suggested that in the comparison of the average migraine days per month, Erenumab (140 mg), Galcanezumab (120 mg, 240 mg), Fremanezumab (225 mg, 675 mg) were superior to placebo, Erenumab(7 mg), and the difference was statistically significant; Fremanezumab (225 mg, 675 mg) was superior to Erenumab (21 mg, 70 mg), and the difference was statistically significant; in the comparison of average medication days of acute migraine-specific drug per month, Erenumab (70 mg, 140 mg), Galcanezumab (120 mg, 240 mg), Fremanezumab (225 mg, 675 mg) was superior to placebo, and Erenumab (140 mg) and Galcanezumab (120 mg, 240 mg) were superior to Erenumab (70 mg), and the difference was statistically significant; there was no statistically significant difference in the average migraine days in the last month or in the medication days of acute migraine-specific drug. Conclusion: Fremanezumab (225 mg) and Galcanezumab (120 mg) may be the best clinical protocol after a comprehensive assessment.